Expert C++/CLI: .NET for Visual C++ Programmers - Heegee, Marcus (Apress, 2012)
Writing this book was only possible because I got a lot of help from people that deserve to be named here. From the team at Apress I would like to thank Elizabeth Seymour, Lori Bring, Jim Huddleston, and Damon Larson. I would also like to thank Stan Lippman, the technical reviewer of my book. His feedback constantly pushed me to make the book better. Without his feedback, the book would have been less correct and much less readable. I also got valuable reviews from Richard Dutton. Several members of the Visual C++ team have been great sources for in-depth information about implementation details of C++/CLI and the CLR. These guys are Martyn Lovell, Brandon Bray, Arjun Bijanki, Jeff Peil, Herb Sutter, Ayman Shoukry, and Bill Dunlap. Many topics that I cover in this book are insights that I got from them. Over the last few years, I have learned a lot about various areas of software development in discussions with my DevelopMentor colleagues, including Dominick Baier, Richard Blewett, Mark Vince Smit, and Mark Smith, as well as from other smart software developers, including Mirko Matytschak, Klaus Jaroslawsky, and Ian Griffiths. Furthermore, I would like to thank the students of my C++/CLI classes. By asking me many interesting questions, they have allowed me to review my knowledge in many different practical contexts.